Monte Carlo simulation and experimental studies on the low temperature characterization of nitrogen adsorption on graphite - Fan, Chunyan; Do, D.; Nicholson, D.; Jagiello, J.; Kenvin, J.; Puzan, M. (Pergamon, 2013)
Adsorption of nitrogen is commonly used to characterise porous carbon solids, and an important prerequisite for a good characterization is that the molecular model for nitrogen should give the correct description of adsorption on a graphite surface over a range of temperatures. To investigate the role of the molecular shape and quadrupole of nitrogen at temperatures below the boiling point we carried out a comprehensive molecular simulation study of the performance of two popular molecular models for nitrogen: (1) 1-site LJ model (1CLJ) and (2) a model with two LJ sites and three partial charges (2CLJ+3q). It was found that, although the 2CLJ+3q model generally gave a better description of the isotherms than the 1CLJ model, when used in Grand Canonical Monte Carlo simulations, it was not able to account for the known spike in the heat curve versus loading at 77 K. When the simulations were re-run in the recently introduced Bin-MC scheme in a canonical ensemble better agreement was found between simulation results and the experimental data for the 2CLJ+3q model over a wide range of temperatures; a result that has not been previously reported in the literature. © 2012 Elsevier Ltd. All rights reserved.